Pengaruh Literasi dan Inklusi Keuangan Terhadap Minat Investasi Di Pasar Modal (Studi Kasus Tenaga Pendidik Di Kota Bogor Tahun 2022): Studi Kasus Tenaga Pendidik Di Kota Bogor Tahun 2022 - Vonny Rezky Amelia Hernawan; Ali Masjono Muchtar (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
The existence of investment interests carried by educators in the city of Bogor is certainly influenced by a number of variables, including financial inclusion and literacy. According to the Financial Services Authority (OJK), a lack of financial literacy can lead to numerous losses in illegal investments. The issue in this study is the significant literacy and inclusion gap that exists in Bogor, a supporting city for the nation's capital. This study aims to investigate the impact of financial inclusion and financial literacy on educators in Bogor City's interest in capital market investing. The data used are quantitative data collected through questionnaires and analysed using the SPSS program using the multiple linear analysis approach. According to the study's findings, financial literacy and financial inclusion of educators in the city of Bogor have a significant influence on their’s investment interest in the capital market.